Presence of Hepatozoon caimani (Apicomplexa: Hepatozoidae) in the “spectacled caiman” Caiman crocodilus (Linneus 1758) in a zoo of Lima, Peru - Rojas, Gianmarco (2011)
The presence of Hepatozoon caimani in a population of Caiman crocodilus in a zoo located in Lima, Peru was evaluated. Blood samples were collected from 10 specimens of both sexes and various ages. The animals were clinically healthy and kept in captivity at the “Parque Zoológico de Huachipa”. Three blood smears were prepared per animal and stained with May-Grunwald-Giemsa 2%. Intraerythrocitic haemoparasites of the genus Hepatozoon were identified and due to the morphological aspect they were considered to be H. caimani.